2016
DOI: 10.1002/ejic.201501206
|View full text |Cite
|
Sign up to set email alerts
|

Bipyridinium‐bis(carboxylate) Radical Based Materials: X‐ray, EPR and Paramagnetic Solid‐State NMR Investigations

Abstract: The zwitterionic 1,1′-bis(4-carboxyphenyl)-4,4′-bipyridinium (bp4pc) has been synthesized and crystals of its hydrated form bp4pc·2H 2 O and of its protonated reduced form H-bp4pc have been obtained. Upon heating, bp4pc·2H 2 O undergoes partial dehydration, leading to bp4pc·H 2 O at 160°C, together with a color change from yellow (room temperature) to green (140°C) and finally to brown (160-180°C). Analysis of bond lengths in the solid state reveals the expected short (d = 1.425 Å) and long (d = 1.485 Å) C-C c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 34 publications
5
9
0
Order By: Relevance
“…The green phase of 2 is very stable, and we have not observed the corresponding nonradical and expectedly yellow state. The intermediate pseudopolymorph, 2·2H 2 O , has been reported to be nonphotochromic without experimental details . We have obtained the dihydrate by different methods, and crystallographic results confirm that the structure is identical to that reported previously (Figure S15).…”
supporting
confidence: 83%
“…The green phase of 2 is very stable, and we have not observed the corresponding nonradical and expectedly yellow state. The intermediate pseudopolymorph, 2·2H 2 O , has been reported to be nonphotochromic without experimental details . We have obtained the dihydrate by different methods, and crystallographic results confirm that the structure is identical to that reported previously (Figure S15).…”
supporting
confidence: 83%
“…We found that irradiation of 2 results in a change of the central C−C bond length from 1.49(7) to 1.45(6) Å. Typically, a shortening of this bond is a diagnostic feature of viologen radicals owing to the delocalization of the single electron over both pyridinium rings [56, 57] . Further to this, we observed a change in the non‐coordinated C−O bond length of the carboxylate fragment upon irradiation, from 1.26(2) Å to 1.204(17) Å in 2 , and 1.237(9) to 1.211(9) Å in 1 .…”
Section: Resultsmentioning
confidence: 51%
“…There are two possible explanations for the observed photochromic behavior: (i) intermolecular electron transfer (from either Cl − or H 2 O), which changes the total charge of the ligand from 0 to −1, yielding V + . radical cations, [50, 56] or (ii) intramolecular electron transfer from the carboxylic acid to the viologen moiety, resulting in a neutral bcbp ligand with two radical centers (one on the carboxylic acid, COO . , and one on the pyridinium moiety, V + . )…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations